The valuation performance of mathematically-optimised equity-based composite multiples - Nel, Soon; Le Roux, Niël (Universidad ESAN. ESAN Ediciones, 2017)
Purpose – This paper aims to examine the valuation precision of composite models in each of six key industries in South Africa. The objective is to ascertain whether equity-based composite multiples models produce more accurate equity valuations than optimal equity-based single-factor multiples models. Design/methodology/approach – This study applied principal component regression and various mathematical optimisation methods to test the valuation precision of equity-based composite multiplesmodels vis-à-vis equity-based single-factor multiples models. Findings – The findings confirmed that equity-based composite multiples models consistently produced valuations that were substantially more accurate than those of single-factor multiples models for the periodbetween 2001 and 2010. The research results indicated that composite models produced up to 67 per cent more accurate valuations than single-factor multiples models for the period between 2001 and 2010 which represents a substantial gain in valuation precision. Research implications – The evidence therefore suggests that equity-based composite modelling may offer substantial gains in valuation precision over single-factor multiples modelling. Practical implications – In light of the fact that analysts’ reports typically contain various different multiples it seems prudent to consider the inclusion of composite models as a more accurate alternative. Originality/value – This study adds to the existing body of knowledge on the multiples-based approach to equity valuations by presenting composite modelling as a more accurate alternative to the conventionalsingle-factor multiples-based modelling approach.

Propósito – Este documento intenta examinar la precisión de la valoración de los modelos compuestos en cada una de las seis industrias clave en Sudáfrica. El objetivo es determinar si los modelos de múltiplos compuestos basados en la equidad producen valoraciones de capital más precisas que los modelos de múltiplos de factor único óptimos basados en la equidad. Diseño/metodología/enfoque – Este estudio aplicó la regresión de componentes principales y varios métodos de optimización matemática para probar la precisión de la valoración de los múltiplos compuestos basados en capital frente a modelos múltiples de factor único basados en acciones. Hallazgos – Los hallazgos confirmaron que los modelos de múltiplos compuestos basados en la equidad produjeron sistemáticamente valoraciones que fueron sustancialmente más precisas que las de los modelos de múltiplos de un solo factor para el período entre 2001 y 2010. Los resultados de la investigación indicaron que los modelos compuestos produjeron hasta un 67 por ciento de valoraciones más precisas que los modelos de múltiplos de factor único para el período entre 2001 y 2010 lo que representa una ganancia sustancial en la precisión de la valoración. Implicancias de la investigación – La evidencia por lo tanto sugiere que el modelado compuesto basado en la equidad puede ofrecer ganancias sustanciales en la precisión de la valoración sobre el modelado de múltiplos de un solo factor. Implicancias prácticas – A la luz de que los informes de los analistas suelen contener varios múltiplos diferentes parece prudente considerar la inclusión de modelos compuestos como una alternativa más precisa. Originalidad/valor – Este estudio se suma al conocimiento existente sobre el enfoque basado en múltiplos para las valoraciones de capital al presentar el modelado compuesto como una alternativa más precisa al enfoque convencional de modelado de factor único basado en múltiplos.
Keywords: Emerging markets; Composite multiples; Mercados emergentes; Equity multiples; Múltiplos compuestos; Equity valuations; Múltiplos de equidad; Valoraciones de acciones; Valuation precision; Precisión de la valoración; https://purl.org/pe-repo/ocde/ford#5.02.04